Münzen in der Logienquelle - Ehling, Kay (Biblische Notizen, 2007)
Coins are mentioned in three passages of Q: 12:6, 12:59 and 15:8-10. 1.) The avssa,ria in Q 12:6 are not Roman asses, but provincial coins, probably assaria coined under Herod Antipas. 2.) In Q 12:59 the correct reading is lepto,n (according to Luke 12:59, not quadrans like Matthew 5:25. 3.) The parable of the Lost Drachm (Luke 15:8-10) derives from Q. Another indication for this is that only in this passage of the New Testament a drachm (drachms) is mentioned.